A 15-year development path of actions towards an integrated management system: description, evaluation and safety effects within the process industry network in Finland. (1st January 2012) - Väyrynen, Seppo; Koivupalo, Maarit; Latva-Ranta, Jukka
The aim of this research was to give a thorough description of the 15-year path towards a more integrated management system within the process industry and its service delivery network. Northern and Central Finland's main units of process industry and their network (Nemployees > 10, 000) comprised the field material for this chain of development projects. The main methods for R&D were gathering information, opinions and suggestions in the companies' benchmarking, trialling and implementing innovative improvements, evaluating and benchlearning. Purchasing and supplying companies within the studied network have been able, on the contrary to the national trend, to show positive long-term evidence in accident statistics. The score results of the quality prize-style safety management are encouraging. A new holistic auditing tool, HSEQ AP is functioning well and is appreciated by companies on both sides, since they are now partners on much higher level of enabling knowledge and skills of management and business.